An Analysis of Students’ Reading Comprehension of Analytical Exposition Text in SMA Negeri 2 Batusangkar - Febrina Fitri; Yenni Rozimela (Universitas Negeri Padang, 2020)
This research is aimed to know the students’ ability and their perceptions toward the difficulties in comprehending analytical exposition text in different levels of questions which based on Barret’s taxonomy of reading comprehension. This research was conducted at SMA Negeri 2 Batusangkar. The population of this research are all second year students in academic year 2019/2020 with the total number 244 students. Based on the population, the sample of this research is 37 students selected using simple random sampling. This research is descriptive quantitative research and used test and questionnaire as the instruments. This research found that the students’ ability in comprehending different level of questions in analytical exposition text was fair because the average score of students was 51,24. The students have good ability in comprehending analytical exposition questions in form of evaluation level. This research also found that students tend to have difficulties in comprehending analytical exposition text in form of inference level.